EFFECTIVENESS OF THE FAMILY CARD ONLINE REGISTRATION SERVICE(KK) IN THE DISTRICT DEPARTMENT OF POPULATION AND CIVIL REGISTRATION BANYUMAS CENTRAL JAVA PROVINCE - Sumarmo Mulyanto; Sartono Sartono; Emilius Gudonohadi (Department of Public Administration, University Wijaykusuma Purwokerto, 2023)
This study was motivated by the discovery of the same problem related problemsto the effectiveness of services provided by the Department of Population and CivilRegistration Banyumas, as there is no certainty the time of completion ofthe documents on population and civil registration, queues are not orderly, theirdiscriminatory behavior in the provision of services to the society, and stillfound a number errors in the making of the family card so it takes longer to fix.Things like this are often an obstacle that is found in the process of making thefamily card in the Department of Population and Civil Registry Banyumas.This study aims to describe the effectiveness of the services provided by theDepartment of Population and Civil Registration Banyumas. this study usesquantitative methods with descriptive type, involving 10 respondents as the samplein measuring the effectiveness of the services provided. Type of data collectedconsists of the data prime and secondary data. The technique of collecting datathrough questionnaires.Based on the results of the study showed that the effectiveness of makingthe family card in the Department of Population an civil registration Banyumasusing the procedures, facilities and infrastructure, the spirit of cooperation andloyalty of the working group.